Budi sejahtera, reliance and resilient at Mak Teh enterprise - Yahya, Rohaziah; Mhd. Sarif, Suhaimi; Ismail, Yusof (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2023)
Mak Teh Enterprise showcases the incorporation of budi sejahtera, reliance, and resilience in a 15-year-old grocery shop. The primary intention was to serve the community with the budi sejahtera through a simple grocery shop. The support from the family and community is vital and has made Mak Teh Enterprise survive. There is no reason for any commercial entity to incorporate budi sejahtera or charitable intention into the business.